IMPLEMENTASI KEBIJAKAN TENTANG KETERTIBAN UMUM DAN KETENTERAMAN MASYARAKAT Studi: Penertiban Pedagang Kaki Lima Oleh Satuan Polisi Pamong Praja Di Kabupaten Nunukan Provinsi Kalimantan Utara - Wandi Damara (Fakultas Hukum Tata Pemerintahan, 2020)
Congestion, inconvenience of road users, garbage dumped arbitrarily causes unpleasant odors to disturb public peace. Control of people who trade as street vendors by Satpol-PP is a procedure for law enforcement. This study aims to explore and obtain a description of policy implementation, inhibiting factors for policy implementation, and efforts to control street vendors. Researchers used exploratory and qualitative design research methods with an inductive approach where the research informants consisted of elements from government and society. Collecting data using interview and documentation techniques. To analyze the research data using Edward III theory in Sobarsono (2020: 92) and a normative approach. The results of this study are that so far the implementation of policies regarding public policing and public order in controlling street vendors by Satpol-PP has not been optimal, and is still constrained in several ways such as: Apparatus Resources, Lack of public awareness. Suggestions to the Regional Government to be able to handle it by guiding and arranging rigid traders five.